‘Spiritalismus vincit Mundum’ Dutch spiritualism and the beginning of psychical research - Kloosterman, Ingrid (Studium, 2014)
The science of psychical research and parapsychology stemmed, among other things, from wonder about the phenomena of spiritualism: manifestations of the deceased through mediums in séances. In the Netherlands, academic psychical research emerged in 1919, when the Studievereeniging voor Psychical Research (SPR) was founded. In this paper, it is argued that a revival of the popularity of spiritualism during the war contributed to the emergence of the Dutch SPR shortly after the First World War had ended. Mass bereavement does not suffice as an explanation for the growth of the spiritualistic movement in the neutral Netherlands in the war years. It is demonstrated that in the writings of spiritualists about the First World War persistent fin-de-siècle themes can be distinguished. Before and during the First World War Dutch spiritualism was dominated by ‘ideologically’ inclined spiritualists and their more ‘critical-scientific’ counterparts were a minority. This had hindered the development of Dutch psychical research. After the war spiritualists shared their hopeful and optimistic perspective of the human soul with scholars leaning towards psychoanalytical and psychomonist ideas. This eventually led to a joint foundation of the Dutch SPR. This alignment between ideological and critical-scientific spiritualists would not last; opinions on how to handle the research subjects (i.e. mediums) remained too distinct.